2010
DOI: 10.1007/s13337-010-0001-4
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of HIV-1 in India

Abstract: Nearly 25 years after the discovery of the human immunodeficiency virus type 1 (HIV-1) effective control of the AIDS pandemic remains elusive. At the root of this challenge is the evolution of this virus to elude immune control. Error-prone nature of replication and retro-transcription is the hallmark of this virus. This fidelity of replication in HIV-1 is due to the absence of proof-reading/repair and post-replicative error correction mechanisms that normally operate during replication of DNA viruses. Advance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…In the present study, all the samples were found to be HIV-1, subtype C. This fact was corroborated by previous studies conducted in India 13 14 , which reported that the most common subtype of HIV-1 in Indian subcontinent was subtype C 15 . In the present study, of the 400 HIV positive, treatment naive HRGs, 16 per cent were found to be recently infected within the past four months.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, all the samples were found to be HIV-1, subtype C. This fact was corroborated by previous studies conducted in India 13 14 , which reported that the most common subtype of HIV-1 in Indian subcontinent was subtype C 15 . In the present study, of the 400 HIV positive, treatment naive HRGs, 16 per cent were found to be recently infected within the past four months.…”
Section: Discussionsupporting
confidence: 91%
“…The predominant HIV strain in India is group M subtype C (Seth, ). Although small molecule inhibitor therapies have been successfully used, they are geared for subtype B, and mutations leading to drug resistance have required development of new line of molecules (Toor et al , ).…”
Section: Efforts To Limit Tti Through Blood Screening In Indiamentioning
confidence: 99%
“…The analyses that have been undertaken to date are based on B clade cohorts in Japan, where the HLA-B*52:01 is relatively prevalent (8)(9)(10)(11). In the current study, we focus on a North Indian population in which HLA-B*52:01 is expressed in more than 20% of subjects (http://www.allelefrequencies.net/) and where the C clade is the predominant subtype (12). To date there have been very few studies investigating the impact of HLA on HIV in India, which has the world's third-highest burden, with 2.7 million infections (12).…”
mentioning
confidence: 99%